Predation on Rattus baluensis (Thomas, 1894) by Trimeresurus sabahi Regenass & Kramer, 1981, in Sabah, Borneo. - Evan S.H. Quah; Alvinus Joseph; Paul Y. Imbun (Department of Biology Victor Valley College, 2025)
The Sabah Bamboo Pitviper, Trimeresurus sabahi Regenass & Kramer, 1981, was first described from Mount Kinabalu, Kulapis River, Sabah, East Malaysia (Regenass and Kramer, 1981; Vogel et al., 2004). The species was previously recognised as endemic to Borneo, but was later found to be more widespread across Southeast Asia after a taxonomic revision by Wostl et al. (2016), who synonymised T. barati Regenass & Kramer, 1981, T. buniana (Grismer et al., 2006), T. fucatus Vogel et al., 2004, and T. toba David et al., 2009 with T. sabahi. These taxa are at present recognised as subspecies of T. sabahi (Uetz et al., 2024), whose nominate form is restricted to Borneo.